2008
DOI: 10.1111/j.1600-0501.2008.01560.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of modifying and veneering the surface of ceramic abutments on cellular attachment and proliferation

Abstract: Although the roughness of all surfaces investigated was <0.4 mum, the study disclosed significant differences in cellular attachment and proliferation associated with the various surface modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…6 Even when differences exist in tested conditioning procedures (particle size or applied distance to the ceramic surfaces) it seems that abrading procedures are less effective on the alumina than on zirconium oxide ceramics. 19 Airborne particle abrasion did not increase roughness on alumina oxide ceramic surfaces due to the high toughness exhibited by In-Ceram Alumina. 6,20 This porcelain has high alumina content and glass infiltrated into a framework.…”
Section: Discussionmentioning
confidence: 96%
“…6 Even when differences exist in tested conditioning procedures (particle size or applied distance to the ceramic surfaces) it seems that abrading procedures are less effective on the alumina than on zirconium oxide ceramics. 19 Airborne particle abrasion did not increase roughness on alumina oxide ceramic surfaces due to the high toughness exhibited by In-Ceram Alumina. 6,20 This porcelain has high alumina content and glass infiltrated into a framework.…”
Section: Discussionmentioning
confidence: 96%
“…2,3 The formation and maintenance of soft tissue barrier mainly depends on the response of peri-implant soft tissues to implant materials. [4][5][6][7] For one-piece implants (tissue level), the critical area is the neck portion of the implants. For two-piece implants (bone level), the critical area is the material and surface of the abutments.…”
Section: Introductionmentioning
confidence: 99%
“…EP were designed to obtain a material with controlled composition by cold isostatic pressing and pre-sintering in order to obtain a Y-TZP inert abutments since it is need to be nontoxic in order to help the attachment and growth of the surrounding gingiva [8]. The composition of EP differs from the others by the presence of titanium oxide (TiO 2 ), chlorine (Cl), iron oxide (Fe 2 O 3 ) and sodium oxide (Na 2 O 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, they are needed for any implant or abutment materials that are not toxic and to be inert to them [7,8]. The formation of the epithelial attachment is influenced by the material composition of the transgingival implant components [8][9][10]. A previous study showed that Ti surfaces may play an important role in modulating the cytokine release in cultured Human Gingival Fibroblasts (HGF) [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation